Characterization of Voltage Generation Obtained from Water Droplets on a Taro Leaf (Colocasia esculenta L) Surface - Ena Marlina; Akhmad Faruq Alhikami; Metty Trisna Negara; Sekar Rahima Sahwahita; Mochammad Basjir (Universitas Islam Riau (UIR) Press, 2023)
Voltage generation was obtained using a water droplet characterization on a taro (Colocasia esculenta L) leaf surface. This method relies on the superhydrophobic effect from the contact angle between the water droplet and the taro leaf’s surface allowing electron jumping and voltage generation. Water droplets were dropped on the top of taro leaf surface equipped with aluminum foil underneath as an electrode. The voltage was measured at various slope angles of 20°, 40° and 60° in a real-time basis. A digital camera was used to capture the droplet movement and characterization. It is found that the taro leaf has a surface morphology of nano-sized pointed pillars which created a superhydrophobic field. The energy generation was primarily obtained from the electron jump which was caused by the surface tension of the nano-stalagmite structure assisted by the minerals contained in the taro leaf surface. The results reported that the smaller the droplet radius (the smaller the droplet surface area), the greater the droplet surface tension and the greater the voltage generation. Furthermore, the highest voltage generation was obtained 321.2 mV at 20°-degree angle of slopes.